Financial cooperation initiatives in Latin America: Conditions of origins, subsistence and eventual vanishing - Alves, Elia Elisa Cia; Biancarelli, André Martins (Economics and Business Review, 2020)
Why do countries engage in Regional Financial Cooperation (RFC) initiatives and why they may give up on them? Under which conditions are those mechanisms born and how may changes affect their performance? Although comparative studies have been a prolific strategy to investigate RFC the focus on the experiences of a specific region may reveal new insights. Therefore the aim of this paper is to map the existing RFC mechanisms in Latin America, seeking to identify the demand, supply and conjectural conditions behind the processes of their creation and evolution. The theoretical framework provides concepts from International Relations’ theories concerning regional institution building. Empirically fourteen Latin American RFC initiatives are surveyed. As a result important variables explaining RFC mechanisms in Latin America are presented in the paper: demand for greater participation (sense of belonging), material and political capacity from a paymaster and macroeconomic coordination.